How to be multiple : the philosophy of twins - De Bres, Helena (Bloomsbury Publishing, 2023)
"Philosophy professor, humorist, and identical twin Helena de Bres takes the curious, wondrous, ludicrous experience of being a twin as a lens through which to reconsider our place in the world and how we relate to others. Which one are you? Are you the same? Can you read each other's minds? Identical twins get the weirdest existential questions from strangers, also from loved ones, in fact, even from themselves. For twins fascinate all of us... including twins. For Helena de Bres, this fascination was never far from philosophy's most unnerving unknowns. What makes someone themselves rather than someone else? What does perfect love look like? Can we really act freely? Drawing from her relationship with her own twin Julia, and accompanied by Julia's line drawings, Helena uses twinhood to rethink the limits of personhood, consciousness, love, freedom, even justice. With her inimitably candid, goofy, brilliant voice, she explores the long tradition of twin representations in art, myth, and popular culture; their "freakish" history; their peculiar social standing; and what it's really like to be one of two. With hope and humor, she argues that our reactions to twins reveal our broader desires and fears about selfhood, fate, and human connection, and that reflecting on twinhood can help each of us-twin and singleton alike-to recognize our own multiplicity, and approach life with greater curiosity, imagination, and courage"--